2007
DOI: 10.1074/jbc.m703997200
|View full text |Cite
|
Sign up to set email alerts
|

Two SCA (Stigma/Style Cysteine-rich Adhesin) Isoforms Show Structural Differences That Correlate with Their Levels of in Vitro Pollen Tube Adhesion Activity

Abstract: Lily pollen tubes grow adhering to an extracellular matrix produced by the transmitting tract epidermis in a hollow style. SCA, a small (ϳ9.4 kDa), basic protein plus low esterified pectin from this extracellular matrix are involved in the pollen tube adhesion event. The mode of action for this adhesion event is unknown. We partially separated three SCA isoforms from the lily stigma in serial size exclusion column fractions (SCA1, 9370 Da; SCA2, 9384 Da; SCA3, 9484 Da). Peptide sequencing analysis allowed us t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 67 publications
0
36
0
1
Order By: Relevance
“…SCA was also shown to be involved in pollen tube chemotropism by synergistically enhancing the activity of lily chemocyanin on the stigma (Kim et al, 2003). Further work revealed that lily SCA, a secreted pistil factor, is endocytosed through the pollen tube tip and may function in tip growth as a signal transducer (Kim et al, 2006;Chae et al, 2007). LTPs related to SCA in other plant species have a variety of proposed biological roles.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…SCA was also shown to be involved in pollen tube chemotropism by synergistically enhancing the activity of lily chemocyanin on the stigma (Kim et al, 2003). Further work revealed that lily SCA, a secreted pistil factor, is endocytosed through the pollen tube tip and may function in tip growth as a signal transducer (Kim et al, 2006;Chae et al, 2007). LTPs related to SCA in other plant species have a variety of proposed biological roles.…”
Section: Discussionmentioning
confidence: 99%
“…These features were also identified in SCA (Chae et al, 2007). Computational modeling indicates that SCA has an LTP-like structure with a globular shape of the orthogonal four-helix bundle architecture and a hydrophobic core (Chae et al, 2007). The hydrophobic cavity of several plant LTPs is known to interact with lipids and fatty acids in vitro without ligand specificity (Zachowski et al, 1998;Charvolin et al, 1999;Douliez et al, 2000aDouliez et al, , 2001Hamilton, 2004).…”
Section: Introductionmentioning
confidence: 91%
See 3 more Smart Citations